Fibrinogen and magnesium combination biomaterials modulate macrophage phenotype, NF-kB signaling and crosstalk with mesenchymal stem/stromal cells. (15th September 2020) - Bessa-Gonçalves, Mafalda; Silva, Andreia M.; Brás, João P.; Helmholz, Heike; Luthringer-Feyerabend, Bérengère J.C.; Willumeit-Römer, Regine; Barbosa, Mário A.; Santos, Susana G.
Abstract: Macrophage behavior upon biomaterial implantation conditions the inflammatory response and subsequent tissue repair. The hypothesis behind this work was that fibrinogen (Fg) and magnesium (Mg) biomaterials, used in combination (FgMg) could act synergistically to modulate macrophage activation, promoting a pro-regenerative phenotype. Materials were characterized by scanning electron microscopy, Fg and Mg degradation products were quantified by atomic absorption spectroscopy and ELISA. Whole blood immune cells and primary human monocyte-derived macrophages were exposed to the biomaterials extracts in unstimulated (M0) or pro-inflammatory LPS or LPS-IFNγ (M1) conditions. Macrophage phenotype was evaluated by flow cytometry, cytokines secreted by whole blood cells and macrophages were measured by ELISA, and signaling pathways were probed by Western blotting. The secretomes of macrophages preconditioned with biomaterials extracts were incubated with human mesenchymal stem/stromal cells (MSC) and their effect on osteogenic differentiation was evaluated via Alkaline Phosphatase (ALP) activity and alizarin red staining. Scaffolds of Fg, alone or in the FgMg combination, presented similar 3D porous architectures. Extracts from FgMg materials reduced LPS-induced TNF-α secretion by innate immune cells, and macrophage M1 polarization upon LPS-IFNγ stimulation, resulting in lower cell surface CD86 expression, lower NFκB p65 phosphorylation and reduced TNF-α secretion. Moreover, while biomaterial extracts per se did not enhance MSC osteogenic differentiation, macrophage secretome, particularly from cells exposed to FgMg extracts, increased MSC ALP activity and alizarin red staining, compared with extracts alone. These findings suggest that the combination of Fg and Mg synergistically influences macrophage pro-inflammatory activation and crosstalk with MSC. Statement of significance: Modulating macrophage phenotype by degradable and bioactive biomaterials is an increasingly explored strategy to promote tissue repair/regeneration. Fibrinogen (Fg) and magnesium (Mg)-based materials have been explored in this context. Previous work from our group showed that monocytes interact with fibrinogen adsorbed onto chitosan surfaces through TLR4 and that fibrinogen scaffolds promote in vivo bone regeneration. Also, magnesium ions have been reported to modulate macrophage pro-inflammatory M1 stimulation and to promote bone repair. Here we report, for the first time, the combination of Fg and Mg materials, hypothesizing that it could act synergistically on macrophages, directing them towards a pro-regenerative phenotype. As a first step towards proving/disproving our hypothesis we used extracts obtained from Fg, Mg and FgMg multilayer constructs. We observed that FgMg extracts led to a reduction in the polarization of macrophages towards a pro-inflammatory phenotype. Also, the secretome of macrophages exposed to extracts of the combination material promoted the expression of osteogenic markers by MSCs. Graphical abstarct: Image, graphical abstract